REFLECTION MESSAGE OF DAKWAH NOVEL HABIBURRAHMAN EL-SHIRAZY IN THE PHENOMENON OF YOUNG CHILDREN HIJRAH MOTIVATION - Mohammad Ikhsan Syuhada (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This article is based on the novel Habiburrahman El-Shirazy, which we already know is very popular in society. These novels are not only a medium for reading, but also a medium for da'wah and even a part of religious authority itself. Here are some of the best-selling novels that are used as references, such as Ayat-Ayat Cinta 1, Ayat-Ayat Cinta 2, When Cinta Bertasbih 1, When Cinta Bertasbih 2, When Cinta is Bertasbih 2, and Earth of Love. An interesting storyline coupled with spices of Islamic values make this novel a life inspiration for all Muslims, including young people. The phenomenon of hijrah is now circulating in society, and has become a culture for young people. And of course the inspiration in this novel will more or less help young people who have just migrated. Because in this novel, all of the characters are young people with various walks of life trying to keep their Islamic values.